Molecular dynamics simulations evidence the thermoresponsive behavior of PNIPAM and PDEA in glycerol solutions - Hopkins, Scott D.; Blaisten-Barojas, Estela (Frontiers in Nanotechnology, 2023)
Polymers exhibiting thermoresponsive behavior above a lower critical solution temperature (LCST) undergo a coil-to-globule phase transition that has many biomedical applications, including biosensing, the control of release devices, and gene or drug delivery systems. In addition, there has been sustained scientific interest in these polymers for their use in industrial applications, including water treatment and desalination. Since the coil-to-globule phase transition is greatly affected by the hydrophilic/hydrophobic balance of the polymer-solvent interactions, the LCST of a particular thermoresponsive polymer depends on the local solvent environment and can be tuned through the modification of solution parameters such as co-solvent molar concentrations or pH. While there have been numerous experimental and computational studies focused on the properties of these polymers in aqueous solutions, study of their behavior in more viscous solvents has been limited. In this research, the thermoresponsive behavior of poly(N-isopropylacrylamide) (PNIPAM) and poly(N,N-diethylacrylamide) (PDEA) has been evaluated when in solution with water, the highly viscous liquid glycerol, and both 50:50 and 90:10 glycerol:water mixtures. The adopted methodology includes molecular dynamics techniques and a modified OPLS all-atom force field, which is particularly challenging when the monomers of the targeted polymers have side-chains consisting of a hydrophobic isopropyl group and a hydrophilic amide group along a carbon backbone chain. Hence, our approach entailed simulations at the microsecond scale.The structural and energetic properties of the polymers were characterized, including radius of gyration, solvent accessible surface area, polymer-solvent hydrogen bonding, and interaction energies. Our predictions indicate that these polymers sustain a coil-to-globule phase transition in glycerol solvents at significantly higher LCSTs when compared to the LCST in less viscous aqueous solutions. These predictions highlight valuable insights that will prove advantageous for industrial and nano-scale applications requiring polymer phase behavior with elevated LCST well above ambient temperature.